Comparação das respostas cardiorrespiratórias entre corredores capixabas de diferentes níveis de desempenho - Milagre, Elaine Dalman (2015)
There are in the literature a large number of studies related to the performance of the runners. However, none of them investigated the level of street runners performance (elite athletes, amateur and non-athletes) so that there is com parison. The main objective was to identify the cardiopulmonary profile of in capixaba street runners maximum effort test. We evaluated 59 subjects of both sexes, state residents of Espírito Santo, Brazil, trained for at least six months in street running, aged from 20 to 45, divided into tree diferent level of performance for homogeneous groups (elite – GE, amateur – GA, and nonathlete – GNA), from a ranking in street running events. All runners underwent a cardiopulmonary exercise test (CPET) using a ramp protocol treadmill (Cortex metalyser 3B), being analyzed in the phases of ventilatory anaerobic threshold (VAT), respiratory compensation point (RCP) and maximum (MAX). Comparisons were made between the three groups by analysis of variance route, followed by post-hoc Tukey (p<0.05). There were significant differences between groups in relation to VO₂ (ml.kg-1 .min-1 ), VE and speed in the VAT, RCP and MAX in both sexes. Among men are higher values for groups with higher performance level at all stages of CPET. In relation women, GE was similar in relation to GA, differing only GNA. To VE no significant differences between groups, as well as the variables VO2 (L.min-1 ), heart rate (HR) and the respiratory exchange ratio (RER), phases of CPET in both sexes. It was concluded that respiratory efficiency and performance characteristics (running speed), among men, are superior to the groups with the highest level of performance. Among women, there is no difference between GE and GA, as well as between GA and GNA.